A pair of new sesquiterpene isomers containing spiro heterocyclic skeleton from plant-derived fungus Botryosphaeria dothidea. (December 2022) - Li, Li; Xu, Guang-Ming; Cai, Jia; Ou, Yang-Lin; Zhao, Bi-Qing; Lv, Zhen-Zhen; Zhou, Xiao-Jiang
Abstract: A pair of new sesquiterpene isomers containing a spiro heterocyclic skeleton, dothimes A (1 ) and B (2 ), together with six known compounds, quindoline (3 ), ( S )-3-(3-indolyl)lactic acid methyl ester (4 ), dankasterone B (5 ), dibutyl phthalate (6 ), (1 S, 3 R, 4 R, 7 S )-3, 4-dihydroxy- α -bisabolol (7 ), and p -hydroxybenzaldehyde (8 ), were isolated from the plant-derived fungus Botryosphaeria dothidea . The structures of all isolated compounds were determined based on extensive spectroscopic analyses, including 1D/2D nuclear magnetic resonance (NMR), and high resolution electrospray ionization mass spectrometry (HRESIMS) data, as well as by comparison with literature reports. Compounds 1 and 2 exhibited inhibitory effects on lipopolysaccharide (LPS)-induced nitric oxide (NO) production with IC50 values of 63.66 and 58.29 μM, respectively. Graphical Abstract: ga1 Highlights: A pair of new sesquiterpene isomers was isolated from Botryosphaeria dothidea . The structures of 1 and 2 were elucidated by spectroscopic analyses. Compounds 1 and 2 showed weak anti-inflammatory activity.